Distributed trusted demand response bidding mechanism empowered by blockchain - Lei Wang; Tong Li; Chao Yang; Jiang Chen; Yang Liu; Shuai Ren (Intelligent and Converged Networks)
In the demand response process involving multi-agent participation, multiple parties’ interests are involved and response execution status supervision is required. Traditional centralized demand response systems lack trust attributes. At the same time, traditional centralized cloud management can no longer support massive terminal services, resulting in delays in demand response services. We build a distributed trusted demand response architecture based on blockchain, illustrating the information interaction process in the demand bidding process and container-based edge-side heterogeneous resource management. We also propose a demand bidding algorithm that takes into account both the day-ahead market and the intraday market, aiming to maximize the aggregator’s benefits. In addition, a virtual resource management algorithm to support demand response tasks is also proposed to optimize computing resource allocation and meet business latency requirements. Simulation results demonstrate that compared with only cloud computing or edge computing, the solution we proposed can reduce response delay by more than 39% for the sample system. Energy cost is saved by about 10.25% during container scheduling.